FORMULASI EMULGEL DARI EKSTRAK DAUN KELOR (Moringa oleifera LAM) SERTA EVALUASI AKTIVITAS ANTIOKSIDAN DENGAN METODE DPPH - Nurul Istiqomah; Juliyanti Akuba; Muhammad Taupik (State University of Gorontalo, 2021)
Moringa (Moringa oleifera Lam) is one of the plants that has high antioxidant activity, especially in the leaves. Emulgel is one of the topical dosage which dermatologically has several beneficial properties, namely thixotropic, not oily, easy to spread, easy to clean, soft, easy to wash, long lasting, transparent and comfortable when used. The purpose of this research was to formulate moringa (Moringa oleifera Lam) leaves extract into emulgel dosage forms and determine the antioxidant activity of the dosage using DPPH method.The research began with extraction of moringa leaves and optimization of the base by varying the concentration of carbopol 940 as gelling consisting of F1 0.5%, F2 1%, F3 1.5% and F4 2%. The base that met the requirements of good physical stability was F2. The F2 base was then made into emulgel dosage with 3 concentration variations of the extract, namely F2a 4%, F2b 5% and F2c 6%. The physical stability test result of each formula met the organoleptic test,the pH test, the dispersion test, the adhesion test, the viscosity test, and the freeze-thaw test. The One way ANOVA statistical test result showed that the p value was greater than 0.05, which meant that the emulgel dosage had good physical stability. The IC50values of each antioxidant activity result were F2a (t0 = 120.464 g/mL; t28 = 144.887 g/mL), F2b (t0 = 113.642 g/mL; t28 = 128.407g/mL), F2c (t0 = 74.745 g/mL; t28 = 90.618 g/mL). The statistical results of the t-test showed thep value = 0,027, (0.05), This indicated that there were significant difference results of the antioxidant activity test between the three formulas on the first day (t0) and on the 28th day (t28).